Articles of Agreement of the International Monetary Fund : Adopted at the United Nations Monetary and Financial Conference, Bretton Woods, New Hampshire, July 22, 1944. Entered into force December 27, 1945. Amended effective July 28, 1969...; amended effective April 1, 1978...; and amended effective November 11, 1992.... - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1993)
Revised in 1993, this edition incorporates the Third Amendment of the Articles of Agreement. Reprinted in December 2004. Reprinted in January 2008 (200 copies).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet